A BOOK REVIEW: ENGLISH AS A FOREIGN LANGUAGE FOR DEAF AND HARD OF HEARING LEARNERS: (Written by Ewa Domagała-Zyśk, Nuzha Moritz, and Anna Podlewska) - Rahmaniar Rahmaniar; Zulkifli Surahmat; Ahmed Sardi (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2023)
The content of this book is intended to address difficulties about teaching technique limits and instructor flexibility when teaching English as a Foreign Language (EFL) to DHH students. This book focuses on conceptual overviews of the importance of inclusive English learning for all students, especially DHH pupils. The authors give two parts of primary research reports on the use of various English learning strategies for DHH learners in diverse circumstances, as well as theoretical studies on approaches to learning strategies appropriate for DHH learners from various perspectives. The initial chapter in this book examines comprehensive input strategies and treatments, including a review of the principles and theories that serve as the foundation for language learning for students with special needs. In the second section, the authors present some research findings on the circumstances and outcomes of teaching EFL to DHH learners.